A Scientometric Profile of Sant Gadge Baba Amravati University, Amravati During 1996-2017 - Bapte, Vishal Dattatray; Gedam, Jyoti (DESIDOC Journal of Library & Information Technology, 2018)
The study presents the scientometric profile of Sant Gadge Baba Amravati University (SGBAU), Amravati during 1996-2017. The required research output for the study has been pulled out from SCOPUS database on the basis of affiliation based search. The complete research output is 1130 with 11.67% average citations per paper. The highest H-index (17) was found in the year 2013. 20.08% documents were produced though international collaboration. SGBAU, Amravati has the largest collaboration with Brazil (69) and United States (21). Authorship pattern predicts collaborative trend. Research papers produced with three authors have got the maximum (4444) citations. Journals (839) and Conference papers (174) are the most popular source type preferred by the faculty of SGBAU for research expression. Mahendra Rai (209), S. K. Omnwar (143) and Anand S. Aswar (94) are the most prolific authors. It is noteworthy that Alka P. Yadav has got 3073 citations for her 17 papers. Most of the articles are published in the domain of Physics and Astronomy (356). With regard to institutional collaboration, the faculty members of the SGBAU have confined themselves to the Maharashtra state most of the time. Data visualization is carried out using VOSviewer